A Randomized, First‐in‐Human, Healthy Volunteer Trial of sutimlimab, a Humanized Antibody for the Specific Inhibition of the Classical Complement Pathway. Issue 4 (13th July 2018) - Bartko, Johann; Schoergenhofer, Christian; Schwameis, Michael; Firbas, Christa; Beliveau, Martin; Chang, Colin; Marier, Jean‐Francois; Nix, Darrell; Gilbert, James C.; Panicker, Sandip; Jilma, Bernd
Abstract : Aberrant activation of the classical complement pathway is the common underlying pathophysiology of orphan diseases such as bullous pemphigoid, antibody‐mediated rejection of organ transplants, cold agglutinin disease, and warm autoimmune hemolytic anemia. Therapeutic options for these complement‐mediated disorders are limited and sutimlimab, a humanized monoclonal antibody directed against complement factor C1s, may be potentially useful for inhibition of the classical complement pathway. A phase I, first‐in‐human, double‐blind, randomized, placebo‐controlled, dose‐escalation trial of single and multiple doses of sutimlimab or placebo was conducted in 64 volunteers to evaluate safety, tolerability, pharmacokinetic, and pharmacodynamic profiles. Single and multiple infusions of sutimlimab were well tolerated without any safety concerns. sutimlimab exhibited a steep concentration–effect relationship with a Hill coefficient of 2.4, and an IC90 of 15.5 μg/mL. This study establishes the foundation for using sutimlimab as a highly selective inhibitor of the classical complement pathway in different diseases.